Perioperative opioid prescriptions associated with stress incontinence and pelvic organ prolapse surgery - WILLIS-GRAY, Marcella (Am J Obstet Gynecol, 2020)
BACKGROUND: There is an opioid epidemic in the United States with a contributing factor being opioids prescribed for post-operative pain following surgery. OBJECTIVES: Among women who underwent stress incontinence and pelvic organ prolapse surgeries, our primary objective was to determine the proportion of women who filled perioperative opioid prescriptions and to compare factors associated with these opioid prescriptions. We also sought to assess the risk of prolonged opioid use through one year after SUI and POP surgery. STUDY DESIGN: Using a population-based cohort of commercially insured individuals in the 2005–2015 IBM Marketscan® databases, we identified opioid naïve women ≥ 18 years who underwent SUI and/or POP procedures based on CPT codes. We defined the perioperative period as the window beginning 30 days before surgery extending until 7 days after surgery. Any filled opioid prescription in this window was considered a perioperative prescription. For our primary outcome, we report the proportion of opioid naïve women who filled a perioperative opioid prescription and report the median quantity dispensed in the perioperative period. We also assessed demographic and perioperative factors associated with perioperative opioid prescription fills. Prior studies defined prolonged use as the proportion who fill an opioid prescription between 90 – 180 days after surgery. We report this estimate, as well as continuous opioid use, defined as the proportion of women with ongoing monthly opioid prescriptions filled through one-year after SUI and/or POP surgery. RESULTS: Among the 217,460 opioid naïve women who underwent urogynecologic surgery, 61,025 (28.1%) had a POP and SUI surgery, 85,575 (39.4%) had SUI without POP surgery and 70,860 (32.6%) had POP without SUI surgery. Overall, 167,354 (77.0%) filled a perioperative opioid prescription, and the median quantity was 30 pills (interquartile range 20, 30). In a multivariate regression model, younger age, POP surgery with or without SUI, abdominal route, hysterectomy and mesh use remained significantly associated with opioid prescriptions filled. Among those with a filled perioperative opioid prescription, the risk of prolonged use, defined as an opioid fill between 90 – 180 days, was 7.5% (95% CI 7.3%,7.6%). However, the risk of prolonged use, defined as continuous use with at least one monthly opioid prescription filled after surgery was significantly lower with the following rates: 1.2% (1.13%, 1.24%), 0.32%(0.29%, 0.35%), 0.06%(0.05%, 0.08%) and 0.04%(0.02%,0.05%) at 60, 90, 180 and 360 days after surgery, respectively. CONCLUSIONS: Among privately insured, opioid naïve women undergoing SUI and/or POP surgery, 77% of women filled an opioid prescription with a median of 30 opioid pills prescribed. For prolonged use, 7.5% (95% CI 7.3,7.6) filled an opioid within 90–180 days after surgery but the rates of continuously filled opioid prescriptions are significantly lower at 0.06% (95% CI 0.05,0.08) at 180 days and 0.04% (95%CI 0.02,0.05) at 1 year after surgery.